Comparative Analysis of Selected Scales to Assess Prognosis in Acute Pancreatitis - Dorota Koziel; Stanislaw Gluszek; Jaroslaw Matykiewicz; Piotr Lewitowicz; Zuzanna Drozdzak (Canadian Journal of Gastroenterology and Hepatology)
OBJECTIVE: To evaluate the utility of selected scales to prognosticate the severity and risk for death among patients with acute pancreatitis (AP) according to the revised Atlanta classification published in 2012.